New data on distribution of the endangered species Viola jooi (Violaceae) in Ukraine - Rolecek, J.; Drevojan, P. (Український ботанічний журнал, 2019)
Here we report the third extant site of Viola jooi in Ukraine. The species was found on an open calcareous scree in the valley of the Tlumach stream near Ostrynia village (Tlumach District, Ivano-Frankivsk Region). Vegetation of the scree may be classified to a broadly circumscribed alliance Stipion calamagrostis or to its east-central European counterpart Teucrion montani (class Thlaspietea rotundifolii). Moreover, our survey of Ukrainian and Polish herbaria revealed several specimens collected during the 1930s at two sites not yet mentioned in the literature, with one of the sites situated near our newly found site. We see a need for a thorough field survey of the historical, extant and other suitable sites of the species in the area of its present distribution in the Ukraine. Despite the new finds, Viola jooi remains one of the rarest relicts of the ancient heliophilous flora of the Volyn-Podolian Upland, pointing to its peri-Alpidic biogeographical affinities. Conservation priorities should be in line with this status.